IMMUNE SYSTEM SUSCEPTIBILITY OF DEPRESSED PATIENTS TO DENGUE VIRUS INFECTION: CASE REPORT - Tri Ratnawati; Doharni Olivia Natasha; Martha Dinar Alit (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Introduction – Depression is a health problem that causes mortality and morbidity. The incidence of depression aged ≥ 15 years is as much as 6.1%. Another health problem is dengue hemorrhagic fever (DHF), where 71,700 confirmed cases of DHF have been reported in Indonesia as of July 2020. The study at Mayo Hospital Lahore explained that there is a correlation between DHF infection and depression. There is no study to describe susceptibility of the immune system of depressed patients to dengue virus infection in Indonesia. Methods – Presented the case of patient, female, 19 years old with initial diagnosis and management of DHF from internal medicine departement. We use a Hamilton Depression Rating Scale (HDRS) questionnaire to evaluated status mental patient. Results – The results of the patient's HDRS questionnaire showed that the patient had moderate depression. The results of the psychiatric examination showed depressive affect, anhedonia, anenergy and feeling useless with an onset 1 month before suffering from DHF. The patient was given pharmacotherapy and psychotherapy from psychiatry. Discuss – Late diagnosis and treatment of depression causes prolonged stress in the body. This condition triggers HPA axis and sympathetic nervous system which will increase levels cortisol, and increased secretion of anti-inflammatory cytokines can reduce inflammatory response to incoming pathogens, so that body will be susceptible to dengue virus infection. Management of depression at a young age with psychotherapy and pharmacotherapy use SSRI and benzodiazepines for reduce the risk of suicide. Conclusion – Late diagnosis and treatment of depression makes immune system vulnerable to pathogens or infections. Interdisciplinary collaboration is needed so that the enforcement of psychiatric cases in hospitalization becomes more accurate and for further research to be carried out on the correlation of depression with the incidence of dengue hemorrhagic fever with a different research design. Keywords: depression, DHF, HPA axis, proinflammatory cytokines, cortisol.